2009
DOI: 10.1021/ie801867t
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility of Fischer−Tropsch Diesel with Petroleum and Soybean Biodiesel Blends

Abstract: The Department of Defense is the largest consumer of middle distillate fuels. It has been recommended that alternative fuel sources be considered as replacements or blending stocks for middle distillate ground transportation and marine fuels. Therefore, the search for suitable replacements or blending stocks is earnestly continuing. Renewable agricultural crops such as soybeans and others are now in the forefront. Nonrenewable synthetic fuels such as those produced by Fischer−Tropsch, FT, synthesis from coal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This active area of study has an impact on high efficiency clean combustion engines, the vanguard of advanced diesel engine design. In most standard vehicles, biodiesel concentrations are limited to a blend of 20% to mitigate the effects of its physical properties being different from those of standard diesel fuel (Mushrush, Willauer et al 2009), such as poor cold flow. In addition, biodiesel has a limited shelf life and can form precipitates and go rancid in storage, causing problems in distribution.…”
Section: Generation Of Fungible Fuels From Plant Oils and New Technolmentioning
confidence: 99%
See 1 more Smart Citation
“…This active area of study has an impact on high efficiency clean combustion engines, the vanguard of advanced diesel engine design. In most standard vehicles, biodiesel concentrations are limited to a blend of 20% to mitigate the effects of its physical properties being different from those of standard diesel fuel (Mushrush, Willauer et al 2009), such as poor cold flow. In addition, biodiesel has a limited shelf life and can form precipitates and go rancid in storage, causing problems in distribution.…”
Section: Generation Of Fungible Fuels From Plant Oils and New Technolmentioning
confidence: 99%
“…Biodiesel, with its high oxygen content, mixes well with standard diesel, but not with purely paraffinic Fischer-Tropsch fuel. The aromatics in standard diesel solubilize the olefinic chains and electron-rich esters, where as tertiary carbons in the Fischer-Tropsch paraffins appear to form stable hydroperoxides with degradation products in the biodiesel (Mushrush, Willauer et al 2009). If the biodiesel contains unreacted free-fatty acids, phase separation and precipitates are likely to form.…”
Section: Feasibility Of Using Plant Oils For Fuels In Comparison Withmentioning
confidence: 99%
“…Because of the storage stability issues noted in the literature [7], refinery designs excluded blending of bio-derived material as fatty acid methyl esters (FAME). It is nevertheless discussed as an avenue for diesel fuel improvement.…”
Section: Diesel Fuel Specificationsmentioning
confidence: 99%
“…The addition of biofuel in the form of FAME has some benefit, although it would be necessary to address the storage stability issues reported in the literature [7]. The FAME that are derived from different oils all have high densities and adequate cetane numbers (Table 27.2) [30].…”
Section: Co-refiningmentioning
confidence: 99%
“…However, it has been reported that blends of LTFT distillate, FAME, and petroleum have storage stability issues [45]. Much work has been done on esterification of plant and animal fats and oils as blending components in diesel.…”
Section: Future Diesel Fuel Specification Changesmentioning
confidence: 99%